Accountant’s Work Ethics in the Light of Empirical Studies: Case from Poland - Magdalena WÓJCIK-JURKIEWICZ; Beata SADOWSKA (Communications of International Proceedings, 2020)
Ethics in the accountant’s profession constitutes an unequivocal value and ethical dilemmas were observed in corporate falls that took place at the beginning of the twenty – first century. These scandals pinpointed decision making problem in accounting where estimates and judgements of professionals are of key importance. The main objective of the study is an attempt to answer the two following research questions: The Authors decided that the purpose of the article is to answer two research questions: 1) Whether those responsible for financial information generating are aware of the responsibility they bear? 2) Whether those people follow ethical values on a daily basis?  The following methods were applied: survey research, comparative analysis, participant observation, critical analysis of the subject literature and deductive inference. The thesis of the study is contained within the statement that the accounting staff are under pressure and stress, that determine the occurrence of ethical dilemmas. The study confirmed the thesis posed in the paper that in solving their ethical dilemmas employees follow conscience and inner morality without consulting the Professional Code of Ethics in Accounting. As a consequence of the study the authors proved that staff lack familiarity with the potential of the Code and how it could assist them in resolving ethical dilemmas.
Keywords: Ethical dilemmas; professional accountants; pilot study; Professional Code of Ethics in Accounting; Poland.